Peripheral vitamin D levels in ankylosing spondylitis: A systematic review and meta-analysis - Diao, Maohui; Peng, Jun; Wang, Daidong; Wang, Hongbo (Frontiers in Medicine, 2022)
Objectives: Previous studies showed conflicting results regarding peripheral vitamin D levels in ankylosing spondylitis (AS). We performed this systemic review and meta-analysis to explore whether vitamin D may influence AS process. Methods: Articles published until March 2022 were searched in databases as follows: PubMed, Web of Science and Google Scholar. The present study included cross-sectional and case-control studies regarding vitamin D levels in AS patients. Studies were excluded according to the following exclusion criteria: 1) we excluded studies which did not provide sufficient information regarding the comparison of vitamin D levels in AS patients and healthy controls (HC). Vitamin D levels in the two group studies should be reported or could be calculated in included studies; 2) meta-analysis, reviews and case reports. STATA 12.0 software was used to make meta-analysis. Standard mean differences (SMD) and 95% confidence intervals (CI) were computed as effect size. Results: The present meta-analysis showed no significant difference in peripheral 1,25-dihydroxyvitamin D3 (1,25OHD) levels between AS and healthy controls (HC) in Caucasian with a random effects model (SMD: -0.68, 95%CI (-1.90, 0.54)). AS patients had lower peripheral 25-hydroxyvitamin D (25OHD) levels compared to HC with a random effects model (SMD: -0.45, 95%CI: (-0.70, -0.20)). AS patients had higher peripheral C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels compared to HC in Caucasian population with random effects models (CRP: SMD: 1.08, 95%CI: (0.78, 1.37); ESR: SMD: 0.86, 95%CI: (0.39, 1.34)). However, no significant difference in alkaline phosphatase (ALP), parathyroid hormone (PTH) or calcium levels were indicated between AS and HC in Caucasian with random effects models (ALP: SMD: 0.07, 95%CI: (-0.41, 0.55); PTH: SMD: -0.15, 95%CI: (-0.56, 0.26); calcium: SMD: -0.06, 95%CI: (-0.39, 0.26)). Conclusion: In conclusion, the study showed an inverse association between 25OHD and AS, which suggest that vitamin D may have protective effect on AS. ESR and C-reactive protein (CRP) are important biomarkers for AS.